Crystal structure and Hirshfeld surface analysis of the chalcone derivative (2E)-3-[4-(diphenylamino)phenyl]-1-[4-(prop-1-yn-2-yloxy)phenyl]prop-2-en-1-one - Sundarasamy Madhan; M. NizamMohideen; Vijayan Viswanathan; Devadasan Velmurugan (Acta Crystallographica Section E: Crystallographic Communications)
In the crystal structure of the title chalcone derivative, C30H23NO2, the molecule adopts an s-cis conformation with respect to the C=O and C=C bonds. The triphenylamine moiety has a propeller-type shape, with dihedral angles between the mean planes of pairs of phenyl rings of 72.1 (6), 69.7 (1) and 65.6 (6)°. In the crystal, molecules are linked by C—H...O hydrogen bonds, forming chains extending parallel to [010]. In addition, weak C—H...π interactions consolidate the crystal packing. One of the phenyl rings of the triphenylamine moiety is disordered over two sets of sites.